E-Catering Sales and Ordering Application in Web-Based Raden Catering Business Using the Prototype Method - Ningrat, Sultan Wahyu; Tundjungsari, Vitri (Jurnal Teknologi Informasi dan Pendidikan, 2024)
The E-Catering application is a means that allows people to sell and buy their catering services. This application is designed to be used through smartphone devices, making it easier for users to order food. Raden Catering, which is located at Jalan Cideng Barat Dalam 12 No.1, RT 06/RW 10 Cideng Village, Gambir District, Central Jakarta, 10150, is an example of a catering business that has been operating for 20 years. Even though it has many customers, the catering ordering process so far is still carried out conventionally through direct communication or telephone, which can be less efficient compared to the use of the internet. Therefore, researchers developed this application so that people can order catering more easily and flexibly through an internet connection. The app consists of two parts, namely an app for customers and an app for admins. The results of the study show that application development can be done iteratively, allowing stakeholders to provide input throughout the development process. Customers can easily browse the menu, choose catering packages, and place orders without the need to visit the office in person or contact directly.